THE REALIZATION OF STRATEGIES OF IMPOLITENESS IN IRAQI FACEBOOK COMMENTS ON COVID_19 - Amenah Firas Hameed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Facebook comments provide a rich source of qualitative data that reflects public opinion and sheds light on how people make decisions and build beliefs. There was a notion of politeness and impoliteness in the world of pragmatics. Every person has a public self-image or a face. They hope that other people will appreciate their appearance.Studying impoliteness can help people understand bad manners and impolite language so they can prevent or regulate their actions when interacting with others.To achieve the research aim and objectives, analyzing this specific data source necessarily requires a well-thought-out methodological approach. The aim of this study is to look into the impoliteness strategies used by Iraqi Facebook users in reference to Covid-19.It investigates how impoliteness strategies are implemented on Facebook comments.The descriptive qualitative method was used in this study.The data was provided from Iraqi Facebook users’ comments in Iraqi real pages on Facebook.